PERAN PEMBELAJARAN PIDATO DALAM MENINGKATKAN KETERAMPILAN BERBICARA SISWA PADA MATA PELAJARAN BAHASA INDONESIA - Lanurti Lanurti; Zena Zena; Nurlisa Nurlisa (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This study investigates how speech learning can help improve students' speaking skills in Indonesian language lessons. Speaking skills are very important in language learning, but many students still lack confidence and are unable to express ideas correctly. Through speeches, students can practice creating and delivering ideas in an organized, clear, and confident manner in front of an audience. The research method uses a literature review by collecting data from journals, books, and scientific sources published between 2020 and 2025 through databases like Google Scholar and ResearchGate. The data is analyzed systematically to build concepts and strategies for using speeches in learning. The findings show that speeches are good for training students to manage intonation, pronunciation, and the structure of idea delivery. The steps include explaining concepts, creating texts, practicing, and evaluating. From previous research, speeches make students more courageous, motivated, and skilled in speaking, while also creating a positive communication atmosphere in the classroom. In essence, speech learning is an innovative method suitable for developing students' speaking skills, in line with the 2013 Curriculum. Teachers can implement this to make learning more fun and efficient, preparing students to face real-world communication. This research serves as a reference for improving Indonesian language learning in the future.